EFFECTS OF PRENATAL DEXAMETHASONE ON TERM INFANTS IN CASES OF MATERNAL ANTEPARTUM HEMORRHAGE: A CROSS-SECTIONAL STUDY - Karan, Rosy; Sharma, Ravi Kumar (Student's Journal of Health Research Africa, 2025)
Background In the past 25 years, the use of prenatal corticosteroids in pregnant women who are about to give birth, typically between 24 and 34 weeks of gestation, has been one of the most important advancements in perinatal medicine. Objectives In this investigation, the effects of maternal antepartum hemorrhage (APH) on the results of term children who were exposed to dexamethasone during pregnancy and those who were not. Materials and Methods The study was a retrospective study that was carried out at Hi-Tech Medical College, Bhubaneswar, Odisha, India. Information about 800 patients was extracted. Records pertaining to female patients suffering from APH who gave birth to a single child at 37 weeks or more. Exclusion criteria included those with premature rupture of the membranes or those who did not receive a full course of dexamethasone. Results The study included 800 pregnant women, 40 receiving antenatal dexamethasone and 760 not. The dexamethasone group had a lower mean maternal age (31.5±4.3 vs. 34.2±4.2 years; p<0.001) and higher rates of gestational diabetes (25% vs. 10.2%; p<0.001) and asthma (7.5% vs. 1.57%; p<0.05). APH, primarily due to placenta previa, was more common (20% vs. 5.2%). Dexamethasone exposure was linked to lower birth weight, Apgar scores, and gestational age at delivery (p<0.05). Conclusion The study concluded that while antenatal dexamethasone for APH was linked to a higher rate of surgical vaginal delivery, an earlier delivery, and a lower neonatal birthweight, it was not linked to SGA newborns, NICU admission, or a low Apgar score. Recommendation Antenatal dexamethasone use should be carefully considered, balancing neonatal benefits against risks like lower birth weight and early delivery, particularly in pregnancies complicated by APH.